The research progress on the impact of pig gut microbiota on health and production performance - Jing Wang; Tiejin Tong; Changqing Yu; Qiang Wu (Frontiers in Veterinary Science)
Porcine gut microbiota plays a crucial role in the health and productive performance of pigs, influencing nutrient absorption, feed conversion efficiency, and ultimately, production profitability. In addition to being the primary site of digestion, the intestine houses the pig’s largest immune organ, where the microbial community is essential for overall well-being. During the piglet stage, the gut microbiota undergoes a dynamic evolution, gradually adapting to the host environment. This plasticity presents opportunities to intervene and optimize its composition from early stages, enhancing animal health and development. Among the key factors in this process, dietary fiber plays a fundamental role, as its fermentation by the gut microbiota directly affects its composition and functionality, particularly in the distal small intestine, colon, and rectum. The short-chain fatty acids produced during this process not only provide continuous energy to intestinal cells but also regulate immune responses, prevent infections, and contribute to the body’s homeostasis, promoting healthy growth. Despite advancements in understanding host-microbiota interactions, there is still no clear consensus on the optimal balance of gut microbiota or a precise definition of a healthy microbiota. Current research aims to identify the factors that modulate the gastrointestinal microbiota and its physiological and immune functions. Future findings will aid in developing strategies to restore gut homeostasis after external disruptions, such as stress, antibiotic use, or infections, thereby improving productivity, reducing stress-related impacts, and preventing diseases in pig production.